1995
DOI: 10.2166/wst.1995.0130
|View full text |Cite
|
Sign up to set email alerts
|

Cold-climate constructed wetlands

Abstract: This paper outlines design considerations for constructed wetlands with horizontal subsurface flow treating domestic wastewater in cold climates of northern latitudes. Particular attention is devoted to the use of a filter medium with high phosphorus adsorption capacity. Experience from two Norwegian multistage systems consisting of an aerobic pretreatment step followed by constructed wetland units indicates purification processes are nearly the same during winter and summer seasons, with quite high removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 3 publications
5
31
0
1
Order By: Relevance
“…With the exception of system 18, these wetlands treat fecal coliform with efficiencies commensurate with results reported for similar systems with different designs (Bhamidimarri et al, 1991;Maehlum et al, 1995;Neralla et al, 2000). Detailed analyses of the data and observer notes for system 18 may imply that cell 2 is responsible for the failure of this system.…”
Section: Fecal Coliformsupporting
confidence: 65%
See 1 more Smart Citation
“…With the exception of system 18, these wetlands treat fecal coliform with efficiencies commensurate with results reported for similar systems with different designs (Bhamidimarri et al, 1991;Maehlum et al, 1995;Neralla et al, 2000). Detailed analyses of the data and observer notes for system 18 may imply that cell 2 is responsible for the failure of this system.…”
Section: Fecal Coliformsupporting
confidence: 65%
“…Nitrogen (ammonia and total nitrogen) and phosphorus are also mitigated but with widely varying efficiencies compared with other pathogens (Nichols, 1983;Mann, 1990;UrbancBercic and Bulc, 1995;Koottatep and Polprasert, 1997;Cronk and Fennessy, 2001). Seasonal changes in load reduction efficiency appear to be minimal (Maehlum et al, 1995;Wittgren and Maehlum, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies in United States have also shown significant removal efficiency by the wetland system (Steer et al, 2005;Huang et al, 2000). Wetlands have been found suitable for tropical climates (Kantawanichkul et al, 1999), and many European countries have found that wetlands can perform reasonably even in cold climates (Maehlum and Stalnacke, 1999;Maehlum et al, 1995;Haberl et al, 1995). Other examples can be found in Sundaravadivel and Vigneswaran (2001) (1) Constructed wetlands (CW) for INDOT rest stop wastewater treatment.…”
Section: Background and Motivationmentioning
confidence: 99%
“…On the other hand, systems with vertical flow show high percentage of removal of NH 3 -N (Kantawanichkul, 1999). Studies have shown that a combination of both types of flow is better than only vertical flow or only horizontal flow systems (White, 1995;Maehlum et al, 1995;Platzer, 1999). This is because vertical flow systems provide aerobic environments to enhance nitrification and horizontal flow systems provide anaerobic subsurface flow environments for denitrification, and nitrogen removal requires both the processes.…”
Section: Previous Workmentioning
confidence: 99%
“…The LWA-or Filtralite-P-based hybrid CWs combined from VSSF and HSSF filters in series and treating domestic wastewater show equally high long-term efficiency in both summer and winter [3,[37][38][39][40]. Likewise, hybrid subsurface flow CWs used for landfill leachate treatment [41], as well as single or 2-stage VSSF and HSSF filters treating municipal effluents [42,43] show equally high performance in summer and winter.…”
Section: Introductionmentioning
confidence: 99%